2013
DOI: 10.1634/theoncologist.18-s2-26
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in Young Women in Latin America: An Unmet, Growing Burden

Abstract: Background. Breast cancer (BC) is the leading cause of malignancy-related deaths among women aged Յ45 years. There are unexplored and uncertain issues for BC in this particular group in Latin America. The aim of this study is to evaluate BC incidence and mortality among young women and related clinicopathological and survivorship aspects in this region. Materials and Methods. Data were obtained from Globocan 2008 and the International Agency for Research on Cancer's Cancer Incidence in Five Continents series p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 34 publications
1
42
0
7
Order By: Relevance
“…Most series in our country come from large public health institutions, such as the National Institute of Cancer. In the present series we found that patient age does not differ from that of women attended to in public institutions, and this is corroborated with observations already published in other series that have established that, on average, breast cancer onset in our country occurs up to one decade earlier than in the USA or Europe 5,10 . The infiltrating canalicular histologic type is not different from that reported by national and international series; however, the immunophenotype was significantly different, in particular with a lower proportion of the most aggressive subtypes, namely, pure HER2 and triple-negative, although in the latter the difference was not statistically significant with regard to the InCan series (12 vs. 17%).…”
Section: Discussionsupporting
confidence: 93%
“…Most series in our country come from large public health institutions, such as the National Institute of Cancer. In the present series we found that patient age does not differ from that of women attended to in public institutions, and this is corroborated with observations already published in other series that have established that, on average, breast cancer onset in our country occurs up to one decade earlier than in the USA or Europe 5,10 . The infiltrating canalicular histologic type is not different from that reported by national and international series; however, the immunophenotype was significantly different, in particular with a lower proportion of the most aggressive subtypes, namely, pure HER2 and triple-negative, although in the latter the difference was not statistically significant with regard to the InCan series (12 vs. 17%).…”
Section: Discussionsupporting
confidence: 93%
“…The early presentation of breast cancer in developing countries has been attributed to the younger demographic composition of these countries 5,11 . For example, a retrospective study was performed at Ahmadu Bello University Teaching Hospital in Nigeria, a country in which approximately 49% of the population is younger than 15 years of age 12 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Despite the assertion that BC is a leading cause of death and disability among women, especially young women [21,22] and that the BC occurs increasingly in younger women in developing countries [23][24][25][26] [28][29][30] even against the recommendations of international medical societies and health authorities regarding the upper age limits for screening [31][32][33]. This would allow more BC grouped under the concept of "overdiagnosis" to be diagnosed [34][35][36].…”
Section: Age Distributionmentioning
confidence: 99%